2021
DOI: 10.3390/foods10050992
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum and Infrared-Assisted Hot Air Impingement Drying for Improving the Processing Performance and Quality of Poria cocos (Schw.) Wolf Cubes

Abstract: The objective of this study was to develop an efficient drying technology for poria cubes in order to improve product quality. Poria cubes were dried using different methods, including air impingement drying, infrared-assisted air impingement drying, vacuum drying, two-stage vacuum drying, and infrared-assisted air impingement drying. The results were compared with those from hot air drying. For the two-stage drying, the tested conditions were the first stage of vacuum drying with temperatures between 65–85 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In assessing dryer energy performance, its thermal efficiency and SEC are considered by dividing the total energy supplied by mass of evaporated water (Nwakuba, Asoegwu, & Nwaigwe, 2016). SEC in the drying process (MJ/kg), which is the energy needed to remove 1 kg water of the moist product was estimated using the following expressions (W. Zhang, Chen, Pan, & Zheng, 2021): SEC=Emwater, where E is the energy consumed during drying in MJ, and m water is the mass of moisture removal during the drying in kg.…”
Section: Drying Kinetics Of Food Materials In Ir and Ir‐assisted Dryingmentioning
confidence: 99%
See 1 more Smart Citation
“…In assessing dryer energy performance, its thermal efficiency and SEC are considered by dividing the total energy supplied by mass of evaporated water (Nwakuba, Asoegwu, & Nwaigwe, 2016). SEC in the drying process (MJ/kg), which is the energy needed to remove 1 kg water of the moist product was estimated using the following expressions (W. Zhang, Chen, Pan, & Zheng, 2021): SEC=Emwater, where E is the energy consumed during drying in MJ, and m water is the mass of moisture removal during the drying in kg.…”
Section: Drying Kinetics Of Food Materials In Ir and Ir‐assisted Dryingmentioning
confidence: 99%
“…Kaveh, Abbaspour‐Gilandeh, and Nowacka (2021) evaluated the SEC for the drying of green pea in convective, IR, microwave, convective‐vacuum, convective‐IR, convective‐microwave, convective‐rotary, IR‐rotary dryers and reported the SEC values in the range of 12.15–215.45 MJ/kg. W. Zhang et al (2021) reported the lowest SEC value of 1.38 MJ/kg during IR‐assisted air impingement drying of poria cubes. Tezcan, Sabancı, Cevik, Cokgezme, and Icier (2021) observed the SEC values of 3.77–4.45 kJ/kg during the thin‐layer drying of dill leaves in a continuous type IR dryer.…”
Section: Drying Kinetics Of Food Materials In Ir and Ir‐assisted Dryingmentioning
confidence: 99%
“…Over 85% of industrial food dryers are convective, with mostly hot air as the media for heat transfer; often resulting in significant levels of changes in product quality from the initial fresh-like form [ 17 ]. Along with food quality retention, energy efficiency is equally important in the drying process, which is why both aspects are the subject of intensive research and development on food science [ 18 , 19 , 20 , 21 ]. Among the technologies currently deployed for the drying of valuable products, freeze-drying is very expensive, and despite the high-quality of its products, its use is limited to high-value products [ 15 , 18 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, because tree nuts are rich in unsaturated fatty acids (Curb et al, 2000;Gecgel et al, 2011;Ros & Mataix, 2006;Virtanen et al, 2014), the oil quality of tree nuts is sensitive to the thermal drying process Chen, Venkitasamy, Zhang, Deng, et al, 2020;Zhang et al, 2020). Thus, the drying practices of tree nuts need to be conduct appropriately and efficiently right after harvesting to ensure the quality, safety, and market value of dried products (Ajith et al, 2015;Chen, 2021;Tavakolipour, 2015;Zhang et al, 2018;Zhang, Chen, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%